algebra 1 & it's hard for me so I am seeking the answer. please help!

You need to factor this. First factor out a y^{2}.

Notice:

36y^{2}= (6y)^{2}

25 = 5^{2}

The factorization of a^{2}-b^{2} is always (a-b)(a+b). This is called the difference of two squares.

So by the difference of two squares the factorization is y^{2}(6y-5)(6y+5).

If by chance this is 36y^{4}-25y^{2}=0, then we'd need to take it one step further. With our factorization we set y^{2}=0 to get y=**0**, 6y-5 =0 gives y =
**5/6**, and 6y+5 =0 gives y = **-5/6**.

Hope this helps!

-Devin

## Comments

I need more explanation of what you are doing with the expression. For example, does this equal something or does it need factored?

does not equal anything.

Are you supposed to factor it?

gets factored!